Reconocimiento de personas para el ecu-911 de Loja aplicando técnicas de visión artificial. - Cale Pilco, Diego Armando, Verónica Paulina Chimbo Coronel (2015)
Artificial vision has become one of the widest fields of study that may exist, currently applied to different areas such as biometrics, human-computer interaction, cameras, recognition by means of infrared light, reality virtual, detection and face recognition, among others [1]. As for the detection and face recognition the artificial vision has reached a tremendous growth due to application needs-oriented security and surveillance in different areas such as: access control, research process, forensic, commercial software, etc. allowing decreasing the time of completion of the processes involved in making them. In this research it is proposed a module of people recognizing that enables intelligent people search by IP cameras or video, so the manual search process today causes loss of time and resources proposed would replace, for obtaining the best results, analysis of computer vision techniques performed, such as: eigenfaces, Fisherfaces, Local Binary Patterns Histograms, establishing the best suited to different lighting changes and changes in the angle of approach to the camera and image quality. So in developing the content of the literature review shows the bibliographic collection that allows for the main perceptions authors about artificial vision and the different techniques, being a benefit when developing applications based on this approach is presented. Also, the light-heavy ICONIX methodology was used, which could be obtained in the requirements analysis phase the initial requirements were identified: functional and non-functional, technological requirements such as: hardware and software environment. at this stage the initial domain model is also obtained, the use case diagram and finally is presented the prototype graphical user, interfaces in the design phase of the detailed description of the use cases is obtained, the update of model of final diagrams domain of sequence and finally in the implementation phase it is develops the diagram components and code generation. Each of the phases carried out within this project has yielded the results needed to achieve each of the objectives and obtain the Recognition Module for people for Ecu 911 using artificial vision techniques.